Right-to-water Alliances in Indonesia and Two Critical Disjunctions - Wijanto Hadipuro; Prathiwi Widyatmi Putri (PCD Journal, 2020)
Discourses on the right to water have shaped the opposition movement against Indonesia's market-oriented approach. We document how global debate against the privatisation of water has influenced discourses in this sector since 1998, and how activists have utilised such discourses in the context of national and provincial water policy. Our observations and analyses are centred on the decision of the Indonesian Constitutional Court February 2015 to annul the 2004 Law on Water Resources (UU No 7 Tahun 2004 tentang Sumber Daya Air), the legal umbrella under which private water concessions were sanctioned. We seek to understand discourse formations before and after the decision that helped end Indonesia's partial water privatisation. By deploying a textual-oriented discourse analysis of the pros and cons of the right-to-water and market-oriented approaches, this article examines the trajectory of Indonesian social movements opposed to water privatisation. It draws on leading Indonesian newspapers, grey literature—works produced outside academic and commercial publishing—and scientific publications. This article shows that there are limits to the use of the right-to-water discourse among activists, resulting in two critical disjunctions. First, an excessive focus on normative struggles against the privatisation of piped-water services has hindered more progressive, community-oriented responses to market-oriented water policies. Second, social movements in this sector have been disconnected from more recent global agendas for just water governance.